PERAN KOMPETENSI MANAJERIAL DALAM MEMODERASI HUBUNGAN GOOD CORPORATE GOVERNANCE DAN BUDAYA ORGANISASI TERHADAP KINERJA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN SUKAWATI - Ni Luh Putu Wulantari; I Wayan Sudiana; Ni Made Wisni Arie Pramuki (UNHI Press, 2022)
This study aims to determine the effect of good corporate governance and organizational culture on the performance of Village Credit Institutions (LPD) in Sukawati District and to determine the role of managerial competence in moderating the relationship between good corporate governance and organizational culture on the performance of Village Credit Institutions (LPD) in Sukawati District. The population in this study were 33 LPDs in Sukawati District with 99 respondents consisting of the Head of the LPD, the LPD Treasurer and the Chair of the LPD Internal Supervisory Board. The sampling technique used in this study was saturated sample technique so that the entire population was used as the sample, namely the sample obtained in this study was 99 respondents. The data analysis techniques used in this study were descriptive statistical tests and Partial Least Square (PLS) analysis. The results of this study indicate that good corporate governance and organizational culture have a positive and significant effect on LPD performance. Meanwhile, the interaction between managerial competence with good corporate governance has a positive and insignificant effect on LPD performance and the interaction between managerial competence with organizational culture has a negative and insignificant effect on LPD performance.